Co-Expression of the Epstein-Barr Virus-Encoded Latent Membrane Proteins and the Pathogenesis of Classic Hodgkin Lymphoma - Katerina Vrzalikova (Cancers, 2018)
The Epstein-Barr virus (EBV) is present in the tumour cells of a subset of patients with classic Hodgkin lymphoma (cHL), yet the contribution of the virus to the pathogenesis of these tumours remains only poorly understood. The EBV genome in virus-associated cHL expresses a limited subset of genes, restricted to the non-coding Epstein-Barr virus-encoded RNAs (EBERs) and viral miRNA, as well as only three virus proteins; the Epstein-Barr virus nuclear antigen-1 (EBNA1), and the two latent membrane proteins, known as LMP1 and LMP2, the latter of which has two isoforms, LMP2A and LMP2B. LMP1 and LMP2A are of particular interest because they are co-expressed in tumour cells and can activate cellular signalling pathways, driving aberrant cellular transcription in infected B cells to promote lymphomagenesis. This article seeks to bring together the results of recent studies of the latent membrane proteins in different B cell systems, including experiments in animal models as well as a re-analysis of our own transcriptional data. In doing so, we summarise the potentially co-operative and antagonistic effects of the LMPs that are relevant to B cell lymphomagenesis.